EXPERIMENT ON FISSION STIMULATION OF HOLOTHURIA ARTA (HOLOTHUROIDEA, ECHINODERMATA): CHANGING IN BODY WEIGHT AND MORPHOLOGY - Purwati, Pradina; Dwiono, Sigit A.P. (Marine Research in Indonesia, 2007)
Experiment on Holothuria atra provided evidence that asexual reproduction by fission was possible to be stimulated at laboratory. The success of the experiment was determined based on the high survival of stimulated individuals that grew into intact. After being tightened, induced individuals divided into anterior- and posteriorend individuals. During regenerating into intact individuals, the body weight decreased to relatively minimum weight. Developing of new tentacles in posterior-end individuals and anal aperture in anterior-end individuals required 7-8 weeks after fission. These indicators may lead to anatomical recovery which may be a sign of feeding necessity.